Immuno‐Haematological and Growth Responses of Nile Tilapia (Oreochromis niloticus) Exposed to Agricultural Effluents During Dry Season in Benin's Cotton Basin - Abdou Orou‐Seko; Rodrigue Orobiyi Edéya Pèlèbè; Alexis Houndji; Prudencio Tachégnon Agbohessi; Aliyou Yarou Lafia; Abdullateef Ajadi; Akeem Babatunde Dauda; Denis Worlanyo Aheto; Ibrahim Imorou Toko (Aquaculture, Fish and Fisheries, 2025)
ABSTRACT Pesticide residues pose a significant risk to aquatic ecosystems, fauna and human health. Yet, the physiological impact on aquatic organisms, especially fish exposed to pesticide residues in the dry season, remains unexplored, and even data on chronic exposure to pesticide residue mixtures under natural environmental conditions remains scarce. This study evaluated the immune, haematological and growth responses of Oreochromis niloticus exposed to cotton field effluents under in‐situ conditions during the dry season in the Batran water reservoir. A 56‐day experiment was conducted during the dry season using a 2 × 1 design (pen culture system × two environments). The Batran water reservoir in Benin's cotton basin (effluent‐exposed site) was used as a test (polluted) environment, and a concrete tank at the Station de Recherche et d'Innovation en Aquacultures (SRIA) of the University of Parakou represented the controlled environment. The results revealed that O. niloticus exposed to the polluted environment showed significantly lower macrophage activity compared to the control (p > 0.05). The haematological analysis showed elevated eosinophil and heterophil levels in the polluted environment compared to the controls (p < 0.05). On the growth parameters, generally, O. niloticus exhibited higher growth performance in the polluted environment compared to the control, with a significant difference only with the final average weight (83.61 ± 16.61 g; 69.44 ± 5.73 g, respectively) (p < 0.05) at the end of the experiment. These findings imply that the absence of pesticide application during the dry season at Batran likely reduced pollutant‐induced physiological stress, thereby enhancing growth despite comparable immune metrics. These findings suggest the need to contextualise aquaculture management strategies within seasonal agrochemical use cycles, as non‐application periods may offer critical recovery intervals for farmed species.